Comparison of contralateral muscle excitation in proximal versus distal muscles in the upper extremities - Nynes, Alexander; McGhie, David; Aune, Morten A.; Aune, Tore Kristian (Frontiers in Human Neuroscience, 2025)
IntroductionThe purpose of the study was to investigate potential differences in contralateral muscle excitation in proximal versus distal muscles in the upper extremities. Based on the different neuroanatomical and neurophysiological constraints in the central part of the neural system for proximal and distal muscles, it was hypothesized that contralateral muscle excitation (CME) would be higher for proximal than distal muscles.MethodsThirteen university students participated in this study. The participants performed isometric flexion movements with the shoulder and index finger of the dominant arm at four different relative force levels (25, 50, 75, 100%). Force was measured with a force transducer connected to the index finger and elbow on the dominant arm. Muscle excitation was measured using sEMG placed on the flexor carpi radialis (distal condition) and the anterior deltoid (proximal condition) on the non-dominant arm.ResultsCME was observed in both proximal and distal muscles, with proximal muscles displaying significantly higher CME at higher force levels (50, 75, and 100%). In the proximal condition, contractions with the dominant anterior deltoid were associated with a progressive increase in CME across force levels in the contralateral homologous muscle. In contrast, for the distal condition (flexor carpi radialis), CME changes were only evident when comparing the lowest and highest force levels.ConclusionThe results are in coherence with the differences in neuroanatomical and neurophysiological constraints for bilateral communication for proximal versus distal muscles. The present results encourage further neurophysiological studies using direct brain activity measures to explore the potential link between the differences in bilateral communication and CME for proximal versus distal muscles.